Kedudukan Kepolisian Republik Indonesia Sebagai Pelaksana Tugas Gubernur Dalam Sistem Pemerintahan Di Indonesia - Desy Purwaningsih; A Salman Maggalatung (JOURNAL of LEGAL RESEARCH, 2019)
Abstract:The Minister of Home Affairs involves an active police officer to occupy a position in the government, without retiring or quitting his position in the police. Security in West Java when the 2018 regional election was the reason for the Ministry of Home Affairs to appoint M Iriawan as Acting. Governor. In addition, as a police officer, he should maintain his neutrality as a tool of national security and defense in accordance with Article 28 Paragraph (1) of Law Number 2 Year 2002 concerning the National Police of the Republic of Indonesia. Active police officers who occupy positions in government make the public and legal experts worry and doubt their neutrality as state officials. Polri which is responsible for policy and neutrality from practical political activities, for state security does not have to go directly into the government, because every element of the institution in Indonesia must have their respective duties and authorities that must be in accordance with the procedureKeyword: Acting Governor. Active Police Officer